The Degree of Practice of Mathematics Teachers for Electronic Games and their Relationship in Developing the Problem-Solving Skills among Students from the Perspective of Teachers - An Empirical Study on the Public Schools in the Capital Amman- - Liswi, Wafa' Mohamad (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the degree of practice of mathematics teachers for electronic games and their relationship in developing the problem-solving skills among students from the perspective of teachers – an empirical study on the public schools in the capital Amman. A descriptive correlative approach was used. The sample was taken randomly to represent the sample population, which consisted of teachers working in the public schools in the capital Amman totalling (252) teachers. The results of the study revealed that degree of the practice of mathematics teachers for electronic games in public schools in the capital Amman from the perspective of teachers was moderate. Furthermore, the level of problem-solving skills among students of public schools in the capital Amman from the perspective of teachers was also moderate. The study recommended that Educational departments must provide a solid infrastructure, including computer labs and the Internet, to promote the use of electronic games in the educational system.
Keywords: mathematics; electronic games; problem; problem-solving skills; Jordan